Recurrent Henoch Schönlein purpura without renal involvement successfully treated with methotrexate. Issue 2 (May 2019) - Miray Kisla Ekinci, Rabia; Balci, Sibel; Serbes, Mahir; Duyuler Ayçin, Gulsah; Dogruel, Dilek; Ufuk Altintas, Derya; Yilmaz, Mustafa
Introduction: Henoch Schönlein purpura is characterised by palpable purpura, abdominal pain, arthritis/arthralgia, often with a self-limiting course. Herein, we report a patient with recurrent Henoch Schönlein purpura and severe gastrointestinal involvement, successfully treated with methotrexate. Case presentation: A 12-year-old boy was admitted to our department with palpable purpura, abdominal pain and arthralgia. Since gastrointestinal complaints were severe, systemic steroids were administered, with tapering of dosage. Henoch Schönlein purpura recurred several times with severe abdominal pain, maelena and purpura during next two months. Colchicine and hydroxychloroquine were initiated. After four months, we also introduced methotrexate, which enabled discontinuation of previous medications including corticosteroids. Methotrexate was ceased four months later, and remission was sustained without any medications for 24 months. Conclusion: Besides the conflicting data regarding the use of methotrexate in recurrent Henoch Schönlein purpura, our case introduces successful methotrexate experience in a child with Henoch Schönlein purpura and recurrent severe gastrointestinal involvement.